The Heritage of Administrative Politics Model of Traditional Malay Kingdom and Modern Malaysia Government - Ku Hasnan Ku Halim; Iskandar Hasan Tan Abdullah (Human Sustainability Procedia, 2024)
This study looks at the basic administrative politics model from the early civilization of the Malay World to the modern Malaysian administrative politics model. Literature Review are based on secondary documents and previous author's reference to the administrative politics structures that shaped the Traditional Malay Kingdom administration prior to before arrival of Islam and after the arrival of Islam. The methodology used is qualitative and a description of each administrative politics model of the Malay kingdoms that existed in the Malay world, especially Malay Peninsula. The findings show that there are similarities and continuities between the traditional Malay Kingdom administrative politics model before Islam and after Islam. A major change occurred when the British introduced the administrative politics model based on the Westminster system model and the Constitutional monarchy. This led to the continuation of the administrative politics model of the administration inherited for thousands of years to halt when the country achieved independence in 1957. A more thorough study had to be carried out to look at the overall course of the administrative politics model of the Traditional Malay administration. In order for the legacy of governance knowledge and administrative politics model of this administration to be preserved and reused in today's situation. This is very important in solving the problems of in certain governance of administrative politics that happened today through the past heritage of knowledge.